2019
DOI: 10.1001/jama.2019.14901
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Postextubation High-Flow Nasal Oxygen With Noninvasive Ventilation vs High-Flow Nasal Oxygen Alone on Reintubation Among Patients at High Risk of Extubation Failure

Abstract: High-flow nasal oxygen may prevent postextubation respiratory failure in the intensive care unit (ICU). The combination of high-flow nasal oxygen with noninvasive ventilation (NIV) may be an optimal strategy of ventilation to avoid reintubation. OBJECTIVE To determine whether high-flow nasal oxygen with prophylactic NIV applied immediately after extubation could reduce the rate of reintubation, compared with high-flow nasal oxygen alone, in patients at high risk of extubation failure in the ICU. DESIGN, SETTIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
218
1
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 227 publications
(235 citation statements)
references
References 27 publications
4
218
1
12
Order By: Relevance
“…The fact that hypercapnic patients may benefit more from this therapy is consistent with previous data showing that prophylactic NIV after extubation in hypercapnic patients resulted in lower rates of post-extubation respiratory failure and mortality 88 . This RCT suggests that the combination of NIV with HFNT during breaks from NIV provides the best support after a planned extubation for mechanically ventilated patients at higher risk of re-intubation, especially in those with hypercapnia 93 .…”
Section: Barcelona Respiratory Networkmentioning
confidence: 84%
See 1 more Smart Citation
“…The fact that hypercapnic patients may benefit more from this therapy is consistent with previous data showing that prophylactic NIV after extubation in hypercapnic patients resulted in lower rates of post-extubation respiratory failure and mortality 88 . This RCT suggests that the combination of NIV with HFNT during breaks from NIV provides the best support after a planned extubation for mechanically ventilated patients at higher risk of re-intubation, especially in those with hypercapnia 93 .…”
Section: Barcelona Respiratory Networkmentioning
confidence: 84%
“…Very recently, another large multicentre RCT has been conducted with the hypothesis that both NIV and HFNT could be synergistic 93 . The investigators compared the use of prophylactic intermittent NIV intercalated with HFNO versus HFNO alone in 641 patients from 30 ICUs at high risk for post-extubation failure.…”
Section: Barcelona Respiratory Networkmentioning
confidence: 99%
“…The study suggests that systematic assessment of ICUacquired weakness using MRC sum-score should be daily integrated in the decision to extubate, in order to identify patients at high risk and to apply an appropriate strategy of ventilatory support after extubation. Prophylactic non-invasive ventilation immediately after extubation may be an optimal strategy of oxygenation to avoid reintubation in patients at high risk of extubation failure [4,5]. Likewise, prophylactic non-invasive ventilation may be beneficial by avoiding reintubation in patients with ineffective cough, whereas it seems to have no beneficial effects in those with effective cough [10].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent international clinical practice guidelines recommend the use of non-invasive ventilation immediately after extubation to prevent respiratory failure in patients at high risk of reintubation [3]. In patients older than 65 years or having any underlying cardiac or respiratory disease, a recent large randomized clinical trial showed that a combination of high-flow nasal oxygen alternating with non-invasive ventilation was the most efficient strategy to prevent reintubation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…17 In terms of HFNC use in COPD, there are few studies that include use of HFNC in COPD patients with acute respiratory failure, thus further studies are needed. We believe that utilizing HFNC when a patient has hypercapnia (a common occurrence in COPD) should be avoided when possible because the data are limited or have failed to show benefi t. 16,18 COPD patients are particularly at risk for poor nutritional status 19 and skeletal muscle loss, or sarcopenia. 20 Those who develop ARDS from COVID-19 often require mechanical ventilation, and adjunct therapies for ARDS including neuromuscular blockade are both associated with intensive care unitacquired weakness.…”
mentioning
confidence: 99%